Kadrovske potrebe in potencial izobraževanja v lesarstvu - Kropivšek, Jože (Les (Ljubljana), 2024)
To advance the wood sector, which must adapt to social and economic developments, and to manufacture products with higher added value, use modern technologies and introduce digital and sustainable business models in company operations, the wood industry needs an educated staff with appropriate competences. The main objective of the research was thus to analyse the labour demand and educational structure and to identify the potential of education in the wood sector in Slovenia. In the course of the research, we were able to prove a connection between the educational structure of employees and the business success of companies in this sector. We also found that in parallel with the increase in the number of employees in the wood industry, the demand for labour with a wood science and technology education, of all levels, is also increasing. The potential for developing wood science and technology education in Slovenia is therefore great, but it is important that the development of educational programmes involves not only the educational institutions, which must offer modern programmes and implementation methods, but also the business community, which is involved in the implementation of research, defines the needs, and takes care of the promotion of the various branches and professions in the wood sector, with the support of the state, which must above all ensure the systematic creation of material and personnel conditions that enable a high-quality education in this field.
Keywords: business performance; education; izobraževanje; kadri; kadrovske potrebe; labour demand; lesarstvo; personnel; poslovna uspešnost; Slovenia; Slovenija; wood industry